INNOVATION OF ALTERNATIVE SUPERVISION PRACTICES FOR COMPLETION OF ACTION RESEARCH PROJECT IN COVID-19 PANDEMIC SITUATION – A STUDY BASED ON THE BACHELOR OF EDUCATION (HON.) IN SPECIAL NEEDS EDUCATION (BEDSNE) OFFERED BY THE OPEN UNIVERSITY OF SRI LANKA (O (Isagoge - Journal of Humanities and Social Sciences, 2022)
Supervision plays a vital role in the completion of the research project in the bachelor’s degree programmes (Askew et al., 2016). Changes in the delivery of research programmes at the university level have, in recent years, resulting in significant changes to research supervision (McCallin & Nayar, 2012). Especially, the global pandemic COVID-19 has forced academics to be engaged to find out alternative strategies to supervise their students (Wisker, et al. 2021). On other hand, the Covid-19 pandemic had negative effects on the process of research of the programmes (Boufenchoucha & Chandra, 2021). The aim of this study is to innovate the Alternative Supervision Practices for Completion of the Action Research Projects of the BEDSNE programme offered by OUSL during the COVID-19 Pandemic Situation. A fully qualitative approach was followed to conduct this study and a multiple case study design was utilized to conduct the study. The target population was 86 students, and 4 students were supervised by a particular supervisor selected by using the convenience sampling method. Data was collected using reflective journals and semi-structured in-depth interviews. The thematic analysis technique was utilized to analyse the data. The findings: all four students lack knowledge and never skills in action research. Online supervision support to get regular support from the supervisor, time management, managing unnecessary cost, peers, and family members. ZOOM is good for meeting with the supervisor, email is good for sharing the documents with the supervisor and getting immediate feedback from the supervisor, and social media support for the communicating with supervisor and getting support from peers. Online supervision has more advantages than onside supervision. Conclusion: online supervision is more appropriate to supervise the action research of bachelor students in the Open and Distance Education (ODL) mode. Recommendation: supervisors can use online supervision strategies to supervise students in prevailing situations such as the COVID-19 pandemic and the economic crisis of Sri Lanka.
Keywords: Online supervision; Pandemic situation; Action research; Onside